Novice Physician-scientists’ Learning in Communities of Practice - Min-fen Wang; Lori L. Bakken (Adult Education Research Conference, 2006)
This study drew from sociocultural theory to understand novice physician-scientists’ (PSs) clinical research learning experience in the workplaces. The findings suggest that there are various forms of research participation marginalized in the PS-communities. The structural dimension of workplace learning context, such as gender, culture, power, and access needs more attention.
Keywords: Physician-scientist; learning clinical research; community of practice; professional development; workplace learning